PEMBELAJARAN BAHASA INDONESIA PADA SEKOLAH DASAR - Elifia Dwi Utami, Budiman, Widia Azhari Saputri, Wan Ridha Rasyida, Rizky Afifah Alfi, Nadia Rahma; Ros Mardiah Mardiah (Linguistik : Jurnal Bahasa dan Sastra, 2023)
Literature review research related to Indonesian language learning has been carried out before. The problem in this research is that many students still lack the ability to convey good and correct Indonesian. The aim of this research is for learning Indonesian in elementary schools to basically help children to be able to convey using Indonesian. One of the efforts made to understand these goals is to further develop student achievement. The results of this study show that there are still many children who are not fluent in Indonesian due to many supporting factors.